(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
In our article, a new innovative pedagogical technology used in teaching students a foreign language (English) based on a cultural approach is provided. Its teaching priorities and shortcomings are described. It is very effective to use the cultural approach within the framework of the “flipped classroom” pedagogical technology. In particular, the teacher can choose different podcasts that reflect different cultural aspects of the life of English speakers on special educational platforms. In addition, podcasts are often considered to be “flipped classrooms” that help develop the least developed listening skills among students. At the same time, more experiments in this field are needed at the moment, so that later on, based on them, it will be possible to develop complex methods of developing listening skills in students studying a foreign language in linguistic and non-linguistic universities